Designing a multi-epitope vaccine based on MSP1, AMA1, and CSP proteins of plasmodium falciparum 3D7 with TLR4 as adjuvant using immunoinformatic approach - Mim, Maria Akter (2021)
A significant portion of severe malaria cases and deaths are reported all over the world mainly due to Plasmodium falciparum, the deadliest species among all Plasmodium spp. Established and implemented malaria controlling measures becoming less effective as P. falciparum gradually increasing its resistance to most of the primary line anti-malarial drugs. Until so far, the foremost effective vaccine RTS, S/AS01 which was succeeded to reach the phase III trial stage showed less effectiveness in young infants. Therefore, the development of a more effective malaria vaccine that can protect all individuals is urgently required. In this study, an immuno-informatics approach is used to design an effective and long-lasting antibody-inducing multi-epitope vaccine against the erythrocyte stage of P. falciparum targeting merozoite surface protein 1 (MSP1), apical membrane antigen 1 (AMA1) and circumsporozoite antigen (CSP). MSP1 and AMA1 can be synthesized in the mature stage of Plasmodium parasites and involved in the invasion and disruption of red blood cells (RBC) of erythrocyte stage. CSP is one of the most highly expressed proteins on the surface of sporozoites and plays role in hepatocyte invasion as well as further infection toward erythrocytes. After numerous analyses, highly antigenic, non-allergic non-homolog and non-toxic 9 linear B-lymphocyte (LBL), 11 helper T-lymphocyte (HTL) and cytotoxic T-lymphocyte (CTL) epitopes were selected for the final vaccine construct. All the selected HTL epitopes were IL4, IL10, and IFNγ inducer. Two adjuvant motives, Hp91 and RS09 were adjoined via a suitable linker to stimulate the immune response of helper T cell and cytotoxic T cell, respectively. The physicochemical and immunological analysis found that the constructed vaccine was antigenic (antigenicity 0.7725), basic in nature (pI-9.16), soluble (0.905932), hydrophilic (GRAVY-0.842) and non-allergen. Secondary structural features and tertiary structure were predicted using several bioinformatics-based online software. The modeled vaccine was then refined and validated to evaluate the basic nature of proteins. A good binding affinity between TLR-4 (Chain A of 3FXI) and our multi-epitope vaccine was determined by molecular docking. In summary, findings of the immunoinformatic-based analysis had shown acceptable results however further in vivo and in vitro assessments are required to perform on constructed vaccine to confirm its efficacy and safety.